2010
DOI: 10.1159/000323189
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology of Lipid Metabolism in Autism Spectrum Disorders

Abstract: Autism is a neurodevelopmental disorder characterized by impairments in communication and reciprocal social interaction, coupled with repetitive behavior, which typically manifests by 3 years of age. Multiple genes and early exposure to environmental factors are the etiological determinants of the disorder that contribute to variable expression of autism-related traits. Increasing evidence indicates that altered fatty acid metabolic pathways may affect proper function of the nervous system and contribute to au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 251 publications
(194 reference statements)
7
79
0
1
Order By: Relevance
“…25,55,56 Children with autism tend to have a lower level of polyunsaturated fatty acid, which contributes to maintenance of the structural and functional integrity of the central nervous system. [57][58][59][60][61][62][63][64][65][66][67] A double-blind randomized placebo-controlled study found that DHA or eicosapentaenoic acid added to ARA supplementation could reduce behavioural problems in children with autism. [68][69][70] This is consistent with our findings that DHA was significantly associated with CARS score, which measures the severity of autistic behaviours (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…25,55,56 Children with autism tend to have a lower level of polyunsaturated fatty acid, which contributes to maintenance of the structural and functional integrity of the central nervous system. [57][58][59][60][61][62][63][64][65][66][67] A double-blind randomized placebo-controlled study found that DHA or eicosapentaenoic acid added to ARA supplementation could reduce behavioural problems in children with autism. [68][69][70] This is consistent with our findings that DHA was significantly associated with CARS score, which measures the severity of autistic behaviours (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Важливість простагландину E2 для забезпечення раннього нейрогенезу (11-15-та доба ембріонального роз-витку) підтверджується під час проведення експериментів на мишах [24]. В експериментах при нестачі ПГ E2 були виявлені порушення розвитку багатьох мозкових структур.…”
Section: N¹ 4(82) 2016unclassified
“…In an analysis of the FAs composition of red blood cell (RBC) membrane phospholipids showed that the percentage of total PUFA was lower in autistic patients than in controls; and levels of AA and DHA were particularly decreased (p < 0.001) [325]. Reported abnormalities associated with the synthesis of lipid bilayer in ASD as a result of FAs insufficient dietary supplementation or genetic defects can contribute to the symptomatology of autism and individual variety (for review see [326]). A growing body of evidence suggests that individuals who have ASD may have low levels of these PUFAs, particularly DHA and the AA:DHA ratio.…”
Section: Autism -Paradigms Recent Research and Clinical Applicationsmentioning
confidence: 99%